Synthesis and Growth Mechanism of Stable Prenucleated (≈0.8 nm Diameter) PbS Quantum Dots by Medium Energy Ion Scattering Spectroscopy - Park, Young Ho; Park, Seung Min; Jung, Kang-Won; Hwang, Yunju; Sorcar, Saurav; Moon, Dae Woon; In, Su-Il (Materials, 2019)
In the current work, stable prenucleated PbS quantum dots (QDs) with a sub-nanometer (0.8 nm) size have been successfully synthesized via a systematically designed experiment. A detailed analysis of critical nucleation, growth, and stability for such ultrasmall prenucleated clusters is done. The experimental strategy is based on controlled concentration, temperature and injection of respective precursors, thus enabling us to control nucleation rate and separation of stable sub-nanometer PbS QDs with size 0.8 nm. Significantly, by providing additional thermal energy to sub-nanometer PbS QDs, we achieved the fully nucleated cubic crystalline structure of PbS with size of around 1.5 nm. The size and composition of the prenucleated QDs are investigated by sophisticated tools like X-ray photoelectron spectroscopy (XPS) and medium energy ion scattering (MEIS) spectroscopy which confirms the synthesis of PbS with Pb2+ rich surface while the UV-Vis spectroscopy and X-ray diffraction (XRD) data suggests an alternative crystallization path. Non-classical nucleation theory is employed to substantiate the growth mechanism of prenucleated PbS QDs.